KISAH PEMBANGKANGAN IBLIS DALAM AL-QURAN - Latif, Abdul (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2017)
This paper aims to show the stylistics of devil’s disobedience story in Al-Quran . There are seven stories in seven chapters of al-Quran which talk over devil’s disobedience story. This stylistics of devil’s disobedience narratives is analysed by the observation of al-Quran stories within stylistics frame. There were four stylistics which the writer found in this paper. First, the stylistics of this story used four exposure techniques, they were a story began by climax scene, a story began with no preface, a story described by human imagination involve, and a story with insertion of religiousness advices. Second, presentation of story’s elements in this story served all of elements within a story, they were prominent figure, phenomenon, and dialogue. Third, there were three kinds of repetition happened in this story, they were a repetition of story line with the different character, a repetition of story with the different chronology, and a repetition of story with the different language style. Fourth, the art of story description in this story could arouse our mind and psychomotor.  Keywords: Stylistics, Devil’s Disobedience Story, Seven Stories